Flushing and Locking of Venous Catheters: Available Evidence and Evidence Deficit - Godelieve Alice Goossens (Nursing Research and Practice)
Flushing and locking of intravenous catheters are thought to be essential in the prevention of occlusion. The clinical sign of an occlusion is catheter malfunction and flushing is strongly recommended to ensure a well-functioning catheter. Therefore fluid dynamics, flushing techniques, and sufficient flushing volumes are important matters in adequate flushing in all catheter types. If a catheter is not in use, it is locked. For years, it has been thought that the catheter has to be filled with an anticoagulant to prevent catheter occlusion. Heparin has played a key role in locking venous catheters. However, the high number of risks associated with heparin forces us to look for alternatives. A long time ago, 0.9% sodium chloride was already introduced as locking solution in peripheral cannulas. More recently, a 0.9% sodium chloride lock has also been investigated in other types of catheters. Thrombolytic agents have also been studied as a locking solution because their antithrombotic effect was suggested as superior to heparin. Other catheter lock solutions focus on the anti-infective properties of the locks such as antibiotics and chelating agents. Still, the most effective locking solution will depend on the catheter type and the patient’s condition.